Uji Kinerja Mesin Perajang Daun Tembakau Sistem Conveyor Kapasitas 120 Kg/Jam Menggunakan Motor Listrik 1 Hp - Harry Prayitno; Ampala Khoryanton; Gunawan Widodo; Erwan Tri Efendi; Mohammad Ragil Nur Huda; Desna Syarif Syawaludin; Indra Surya Al Muhith; Gutomo; Eni Safriana (Politeknik Negeri Semarang, 2026)
A Small and Medium Enterprise (SMEs) located in Jragung Village, Karangawen, Demak, is engaged in tobacco slicing with a harvest capacity of 400–600 kg. However, the production process is still performed manually using a conventional knife, yielding only 40 kg per day with four employees. This method is inefficient in terms of time, labor, and production output. Additionally, employees have reported health issues due to the prolonged slicing process. To address these challenges and improve productivity, the use of an automatic tobacco slicing machine is necessary. The purpose of this study is to design and develop a tobacco leaf slicing machine utilizing a conveyor system powered by two drive motors. The methods used include a literature review to obtain theoretical foundations and interviews to gather information from relevant sources. The developed machine has dimensions of 530 mm × 810 mm × 1,015 mm and is equipped with two electric motors: one rated at 0.75 HP and 1,400 rpm, and the other at 0.25 HP and 1,420 rpm. Based on test results, the machine achieved an actual slicing capacity of 124.76 kg/hour. The best slicing result was obtained at speed level 2, with slicing uniformity ranging from 2.4 mm to 3.0 mm and an accuracy of 92.29%.